Organizational Commitment as a Mediation between Work Discipline and Organizational Culture on Social Service Employee Performance - Candra Mustika, Rara Ayu; Maksum, Ikhsan (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of work discipline and organizational culture on employee performance with organizational commitment as a mediating variable in the Malang Regency Social Service. The research method used is quantitative with the Partial Least Squares (PLS) approach. The research sample consisted of 56 employees selected using the saturated sample technique. The study's results showed that work discipline positively and significantly affected employee performance, but organizational culture did not significantly influence employee performance. In addition, organizational commitment has been shown to mediate the relationship between work discipline and organizational culture on employee performance. These findings confirm that improved work discipline and a good organizational culture can encourage employee commitment, ultimately impacting performance. The implications of this study provide insight for public sector organizations in developing strategies to improve employee performance through strengthening work discipline, organizational culture, and organizational commitment.